Studi Ketersediaan Airtanah Guna Menentukan Pola Pemberian Air Untuk Kebutuhan Irigasi Di Kecamatan Mojosari Kabupaten Mojokerto - Hariyadi, Achmad; Bisri, Mohammad; Limantara, Lily Montarcih; Sayekti, Rini Wahyu (Fakultas Teknik, Universitas Brawijaya, 2013)
Groundwater is currently one of the alternative to meet the needs of irrigation water. In the Mojosari District there is no surface water irrigation system and there are 7 production wells with 261.33 hectares of agricultural land. How the performance of wells producing seen from the C, Fd and T with wells test and aquifer test. How the pattern schedule of groundwater with rotation method. The aim of this study to plan the pattern schedule of water delivery system with reference to the of the existing plant pattern in Mojosari District.Based on the availability of existing groundwater on the 7 production wells, the first DI Menanggal SDMJ 113 Q = 14 l / dt, A = 20ha (2 blocks), Q planting I 15.39 l / dt (91%), continuously, Q planting II 46.77 l / dt and III Q = 39.76 l / dt (31% and 35%), rotation. Second DI Belahan Tengah SDMJ 521.410 Q = 28 l / dt, A = 92.67 ha (4 blocks), Q planting I 71.31 l / dt, II Q = 212.09 l / dt and III Q = 184.23 l / dt (39%, 13% and 15%), rotationally. Third DI Mojosulur SDMJ 473, 461 Q = 32 l / sec), A = 57ha (4 blocks), Q planting I 43.86 l / dt (73%), rotationally, cropping Q II 130.45 l / dt and III Q = 113.32 l / dt (25% and 28%), rotationally. Fourth source DI Sumber Tanggul SDMJ 283 Q = 12 l / s, A = 50 ha (4 blocks), Q planting I 38.47 l / dt (69%), rotationally, cropping Q II 114.43 l / dt and III Q = 99.40 l / dt (23% and 27%), rotationally. Fifth DI Randubango SDMJ 551 Q = 30 l / s, A = 39 ha (3 blocks), Q planting I 30.01 l / sec (100%), continuously, Q planting II 89.26 l / dt and III Q = 77.53 l / dt (34% and 39%), rotationally. Based on the 7 wells discharge production, the availability of groundwater discharge is sufficient for the needs of irrigation in the district of Mojosari with rotation method.Keywords: existing discharge, wells test, aquifers test, water delivery systems, rotation.